THE NEW HYPOTHESIS ANGULAR DEFORMATION AND FILLING OF DIAGRAMS IN BENDING WITH TORSION IN REINFORCED CONCRETE STRUCTURES - Kolchunov, Vladimir; Dem'yanov, Aleksey; Protchenko, Maxim (Journal of Applied Engineering Science, 2021)
The authors considered a simple method for constructing bend-torsion functionals by grid methods.  Analysis of the diagrams of angular deformations and shear stresses made it possible to develop a new hypothesis of angular deformations. The consequences of the hypothesis were in the form of expressions from the analysis of diagrams. The authors also obtained functionals for determining angular deformations, bending and torque moments from the compressed area of concrete and reinforcement. The projection ratios helped to determine the shear and normal stresses through deformations using diagrams. The filling of the diagrams was in the form of expressions using functionals. The authors recorded expressions for determining the filling of the diagrams, as well as the total bending and torque moments.
Keywords: bending with torsion; functionals; angular deformations; bending moment; torque